Measurement of the occupational risk level specific to workplaces - Călămar Angelica-Nicoleta; Simion Sorin; Kovacs Marius; Simion Alexandru (MATEC Web of Conferences, 2021)
Any workplace implies a greater or lesser number of occupational hazards, respectively workers are exposed to occupational risks, putting their health in danger. If we talk about industrial environments (construction, energy, metallurgy, textiles, wood, etc.), these hazards are found to a greater extent, often exceeding the allowable limit, but occupational pollutants such as dust in suspension and microclimate parameters can also be found in offices, whether they are open space or not. In this sense, the current paper reviews some workplaces and quantifies the level of risk to which workers are exposed to show and demonstrate the importance of occupational health prevention in order not to reach further measures, in time, when these occupational diseases occur. The research conducted led to the conclusion that the determined pollutants (dust, gas, microclimate) exceeded the maximum allowable concentration required by national legislation, both at workplaces in various technological flows and in offices. The high concentrations found in offices are caused by staff traffic, large number of employees, as well as the lack of natural ventilation.